Ismailova E.T., Sadanov A.K., Shemshura O.N., Iskandarova K.A., Sobiczewski P., Molzhigitova A.E. Antibiotic activity of actinomycetes of the genus Streptomyces against the causative agent of the fre blight of fruit crops: Institute of Microbiology and Virology, Kazakhstan, Almaty; Research Institute of Horticulture in Skierniewice, Poland, Skierniewice (Eurasian Journal of Ecology, 2018)
The article presents the study results of the antibiotic activity of extracts, culture liquids obtainedfrom 20 different strains of actinomycetes of the genus Streptomyces isolated from different types of soilsin the Almaty and Kostanai regions of Kazakhstan, against the causative agent of the Erwinia amylovorafire blight. It was found that the extracts of strains studied inhibited the growth of Erwinia amylovorato a greater or lesser extent. While the extracts of strains No. 7, 9 and 28 isolated from the sandy soilof Ili district of Almaty region possessing the greatest antibiotic activity. The growth inhibition zones ofErwinia amylovora as a result of their effect were 18.3 mm, 21.3 mm and 14.3 mm, respectively. In thevariant with the reference product of the Russian production «Fitolavin», recommended for use againstfire blight of fruit crops and taken for comparison, the average size of the growth inhibition zone of thecausative agent of fire blight was 13.5±0.29 mm, which is 1.57 times less, than in the case of usingthe extract of strain No. 9. These strains can later be used for the development of products intended forbiocontrol over the spread of fire blight of fruit crops in Kazakhstan.Key words: fruit crops, fire blight, actinomycetes, Streptomyces, extract, antibiotic activity, growthinhibition.